Time, uncertainty, and trade flows - José Ansón; Jean-François Arvis; Mauro Boffa; Matthias Helble; Ben Shepherd (Asian Development Bank Institute (ADBI), 2017)
This paper quantifies the impact of international transport time on bilateral trade flows in goods using previously unexploited information drawn from a large dataset on international parcel delivery times. In line with previous work, we find that an extra day spent in international transit reduces bilateral trade by just under one percent at the sample median. In addition, and for the first time in the literature, we examine the impact of time-related uncertainty, which requires traders to hold costly inventories or build costly redundancies into supply chains. We find that a one day increase in international transport time uncertainty reduces bilateral trade flows by just over one percent. Splitting the sample into developing and developed countries shows that international transit time matters primarily for South-South trade, whereas uncertainty is relatively more important for North-North trade. Using new data on trade in intermediate versus final goods, we also find some evidence that time and uncertainty both matter more for movements of intermediates of the type that takes place within global value chains.
Keywords: F13; 330; Industry and trade